2010
DOI: 10.1167/iovs.09-4344
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Nitro-oxidative Stress and Neural Cell Death Suggests a Protective Role for Microglial Cells in TNFα−/−Mice in Ischemic Retinopathy

Abstract: Collectively, the results suggest that improved vascular recovery in the absence of TNFalpha is associated with enhanced astrocyte survival and that both phenomena are dependent on preservation of microglial cells that display an anti-inflammatory phenotype during the early ischemic phase of OIR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 54 publications
1
61
0
Order By: Relevance
“…iNOS synthesizes large amounts of NO (nitric oxide). In brain tissue, excess NO causes neurotoxicity and induces neuronal death [73].…”
Section: Discussionmentioning
confidence: 99%
“…iNOS synthesizes large amounts of NO (nitric oxide). In brain tissue, excess NO causes neurotoxicity and induces neuronal death [73].…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of A2 was observed in retinal horizontal cells of hyperoxia-treated mice [66]. Previous work had suggested that arginase might have a beneficial role in limiting retinal injury in this model [83]. In that study, the authors demonstrated reduced retinal cell death and increased astrocyte survival in TNFα-deficient mice.…”
Section: Arginase and Cns Disease/injurymentioning
confidence: 96%
“…Microglial secretion of NO has been shown to be cytotoxic [41][42][43][44][45] and this is particularly debilitating as neurones have limited mitotic capacities. Modulating microglia responses may limit inflammation and tissue damage within the CNS.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%